Sertraline, citalopram and paroxetine in lactation: passage into breastmilk and infant exposure - Den Besten-Bertholee, Daphne; Touw, Daan J.; Damer, Elvera A.; Mian, Paola; Ter Horst, Peter G. J. (Frontiers in Pharmacology, 2024)
This study aimed to investigate the plasma and breastmilk concentrations for sertraline, citalopram and paroxetine for assessment of the Milk/Plasma (M/P) ratio and Absolute Infant Dose (AID), and to determine actual infant drug exposure through breastfeeding.Subsequently, informed recommendations will be formulated regarding the advisability of breastfeeding in women undergoing treatment with the three most widely used antidepressants.A pharmacokinetic prospective observational study in lactating women and their infants using sertraline, citalopram or paroxetine was performed. Paired breastmilk and plasma samples and single point infant plasma samples were collected to determine antidepressant concentrations.An Area Under the Curve (AUC) based approach with the trapezoidal rule was used to calculate M/P ratios and AID for all three antidepressants by combining all measured concentrations for the same dose.Thirty-seven lactating women and their infants participated in this study. 111 paired breastmilk and plasma samples and 37 single point infant plasma samples were collected. Detectable concentrations of sertraline, citalopram and paroxetine were present in all breastmilk samples. For sertraline and citalopram M/P ratio is above one, indicating higher breastmilk than plasma concentrations, however,. The drug exposure by breastmilk did not lead to detectable plasma drug levels in any of the 15 infants for sertraline, for nine (out of 14) infants for citalopram and for eight (out of nine) infants for paroxetine.Given the well-known benefits of breastfeeding, our findings support breastfeeding of infants by mothers who are taking sertraline, citalopram or paroxetine is safe. Sertraline and paroxetine are the preferred antidepressants during breastfeeding, reaching mostly undetectable infant drug levels..